Analysis of dendritic cell subpopulations in follicular lymphoma with respect to the tumor immune microenvironment. Issue 9 (1st September 2016) - Chevalier, Nina; Mueller, Michael; Mougiakakos, Dimitrios; Ihorst, Gabriele; Marks, Reinhard; Schmitt-Graeff, Annette; Veelken, Hendrik
Abstract: The immune cell composition of the follicular lymphoma (FL) tumor microenvironment is increasingly recognized as an important determinant for clinical outcome. Here, we explored frequency and distribution of dendritic cell (DC) subtypes in relation to regulatory T cells (Treg) by immunohistochemistry in lymph node biopsies from patients with de novo FL. We found that neoplastic follicles contained lower DC and higher Treg frequencies than hyperplastic follicles in control lymph nodes. Treg numbers particularly correlated with the subset of conventional CD11c +  DCs. Additionally, both a high intra- to interfollicular ratio of CD11c +  DCs and increased intrafollicular Treg frequencies were associated with decreased overall survival. This suggests that functional interactions between these cells may be relevant for FL progression/recurrence. The presence of CD11c +  DCs in the tumor microenvironment may assist tumor infiltration by Tregs, thus contributing to the suppression of an otherwise beneficial T-cell-dominated FL microenvironment.